Rheological and textural characteristics of mango jam containing different gelling agents - Javanmard, Marjan (2011)
The main objective of this study was to investigate the rheological, textural, optical, and physicochemical characteristics of mango jam with HM pectin, CMC, and sago starch as the gelling agent. The effect of type and concentration of the hydrocolloids namely HM pectin (0.1, 0.7, and 1.2%), CMC (0.5, 1.25, and 2%), and sago starch (2, 6, and 10%) contents on the main characteristics of mango jam such as, physico-chemical properties (aw, and moisture content), optical measurements (L*, a*, b*, and ΔE), textural measurements (hardness and work of shear), rheological properties through steady-shear and dynamic measurements were assessed as response variables. In addition, the treated samples were produced to study the effect of the freeze-thaw treatment on these samples. The results indicated that both the type and concentration of the hydrocolloids affected the physico-chemical properties of the modified mango jams compared to the control. The water activity and moisture content were both influenced significantly (p < 0.05) in terms of there concentration levels. Colour measurements of mango jams containing sago starch seemed to be whiter (L*) and less yellow (b*) in both untreated and treated samples compared with those HM pectin and CMC. The total colour difference showed that the colour characteristics of mango jam prepared with sago starch was not similar with HM pectin and CMC. The textural properties measured revealed that hardness and work of shear in jams containing sago starch were in the same domain as HM pectin and CMC. The hydrocolloid concentration has a significantly influenced (p < 0.05) on both the hardness and work of shear. The effect of freeze-thaw treatment was significant (p < 0.05) on hardness and work of shear in sample prepared with sago starch. However, in HM pectin and CMC, freeze-thaw treatment was not significant (p > 0.05). In steady-state shear measurements of the modified mango jam, the most appropriate rheological model was the Herschel-Bulkley with high goodness of fitting (R2 > 0.9814) for each of the hydrocolloids used in both untreated and treated samples between the three models studied, namely, Power Law, Herschel-Bulkley, and Mizrahi-Berk. The apparent viscosity decreased with temperature while increased with the concentration level. In addition, apparent viscosity decreased in samples that were treated. Dynamic measurements showed that the dynamic moduli (G′ and G″) decreased with temperature but increased with the concentration level in each of the hydrocolloid investigated. Freeze-thaw treatment decreased the loss and storage modulus in each of the hydrocolloids studied. The calculated tan δ value from dynamic measurements was in the range of 0.1 to 1 in most of the frequency window. This result revealed that the samples behaved as weak gels. Thus, in giving an overall picture, sago starch showed similar textural and rheological characteristics as HM pectin and CMC in mango jam as a gelling agent.